2007
DOI: 10.2166/ws.2007.147
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluation of natural coagulants for water treatment

Abstract: In developing countries many people are forced to drink turbid water and as a consequence many children are dying related to water borne diseases. Hence there is a need for inexpensive and easy methods to purify drinking water. The objective of this research is to screen different plant seeds to find a primary natural coagulant able to reduce the turbidity of the drinking water. The protein from 21 different seeds was extracted with water and salt solution and coagulation properties in synthetic clay solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…The thermo-stability of the coagulant protein is in accordance with previous studies conducted on Moringa seed (Ghebremichael et al 2005) and also the case of red bean, sugar maize and red maize (Gunaratna et al 2007). Similar properties have also been described in crude extracts, as well purified proteins of Vigna unguiculata and Parkinsonia aculeata seeds, where the coagulant protein around 6 kDa was found to be thermo-stable (Marobhe et al 2007b).…”
Section: Protein Profile Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The thermo-stability of the coagulant protein is in accordance with previous studies conducted on Moringa seed (Ghebremichael et al 2005) and also the case of red bean, sugar maize and red maize (Gunaratna et al 2007). Similar properties have also been described in crude extracts, as well purified proteins of Vigna unguiculata and Parkinsonia aculeata seeds, where the coagulant protein around 6 kDa was found to be thermo-stable (Marobhe et al 2007b).…”
Section: Protein Profile Analysissupporting
confidence: 90%
“…), sugar maize and red maize (Zea mays sp.) (Gunaratna et al 2007), Jatropha curcas (Pritchard et al 2009;Abidin et al 2013), Nirmali seeds (Strychnos potatorum) (Babu and Chaudhuri 2005), chestnut and acorn (Š ćiban et al 2009) and Cassia angustifolia (Sanghi et al 2002) has been reported. Although several natural materials are reported to be potent coagulant agents, the usage has not become widespread, probably due to limited knowledge and scientific reports on point-ofuse technology (Yin 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the diluted protein extracts showed improved coagulation activity that was lower compared to M. oleifera. Gunaratna et al (2007) also discovered that the protein coagulant was stable at elevated temperatures beyond 85°C with 30 % enhanced activity, but its turbidity removal remained fairly low, which is undesirable for the treatment of drinking water.…”
Section: Phaseolus Angularismentioning
confidence: 99%
“…A number of effective coagulants from plant origin have been identified: Nirmali [8], Okra, red bean, sugar and red maize [9], M. oleifera [10], ManilkaraZapota and a natural coagulant from animal origin; chitosan. The higher coagulant efficiency of natural coagulants allows more active colloidal aggregation and more consistent floc than with synthetic reagents, so that the necessary quantity of product is reduced and also the associated costs.…”
Section: Introductionmentioning
confidence: 99%